2011
DOI: 10.1063/1.3553413
|View full text |Cite
|
Sign up to set email alerts
|

Anomalously large bend elastic constant and faster electro-optic response in anisotropic gels formed by a dipeptide

Abstract: Rheological and morphological properties of reactively compatibilized thermoplastic olefin (TPO) blendsa) J. Rheol. 56, 625 (2012); 10.1122/1.3700966Transversely tapered hybrid electro-optic polymer/sol-gel Mach-Zehnder waveguide modulators

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…It may be recalled here that a factor of 5 increases in the splay elastic constant, and twoorders of magnitude enhancement in the bend elastic constant has been seen in a nematic conned in a gel matrix. 33 Increase of a similar magnitude has also been reported 34 in a ferroelectric liquid crystal conned in a polymer network. These results suggest that the interactions of the LC molecules with the walls of the polymer network perhaps increases the effective elastic constant.…”
Section: Comparison Of the Experimental Data With The Model Predictionssupporting
confidence: 74%
“…It may be recalled here that a factor of 5 increases in the splay elastic constant, and twoorders of magnitude enhancement in the bend elastic constant has been seen in a nematic conned in a gel matrix. 33 Increase of a similar magnitude has also been reported 34 in a ferroelectric liquid crystal conned in a polymer network. These results suggest that the interactions of the LC molecules with the walls of the polymer network perhaps increases the effective elastic constant.…”
Section: Comparison Of the Experimental Data With The Model Predictionssupporting
confidence: 74%
“…It may be recalled that a similar increase in the Frank elastic constant was seen for a nematic in a gel environment. 4 It is possible that the gain in the elastic constant is a standard feature achieved in liquid crystals upon gelation.…”
Section: Dielectric Relaxation Spectroscopy (Drs)mentioning
confidence: 99%
“…Although, as far as connement of LC in a network is concerned, these systems resemble a polymer dispersed LC material, the thermal reversibility of the LC gel is an advantage. The mesophase involved in the investigations on LC organogels has mostly been the nematic, [1][2][3][4] but a few substances with the chiral smectic C (SmC*) phase have also been studied. Kato et al 5a reported the gelating transformation occurring within the smectic region yielding phase sequences of a sol-state 5b smectic to a gel-state smectic.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the interactions between the liquid crystals and the fibrous aggregates properly weaken an alignment force to the LC molecules conveyed from the rubbed-polyimide surfaces, which leads to the faster response [ 36 ]. Another gelator which is a monodisperse homomeric dipeptide also improves the dynamic characteristics of the electro-optical switching of the device employing these gels (compound 5 in Figure 3 ) [ 43 , 44 ]. These effects suggest not just the improvement of response speed, but also two possibilities for new applications of liquid crystals: light scattering displays and memory.…”
Section: New Functional Lc Modulated With Peptidementioning
confidence: 99%